Surgical Outcome Of Obese Living Kidney Donors: A Retrospective Comparative Study - Rashid Bin Hamid; Naranjan Lal; Muhammad Tasadduq Khan; Hammad Mithani; Mohmmad Asim; Sidrah Rashid (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the surgical outcomes among obese and non-obese living kidney donors. Method: The retrospective cohort study was conducted from July to December 2024 at the Renal Transplant Unit of Dow University of Health Sciences, Karachi, and comprised data from January 1, 2020, to June 30, 2024, of living kidney donors aged 18-65 years who had undergone open nephrectomy operations. Individuals with body mass index 25kg/m² or higher were designated as obese donors, while those with body mass index <25kg/m² were taken as non-obese donors. A-priori sample size was calculated (minimum 60); 70 donors met the eligibility criteria and were included through non-probability consecutive sampling. Perioperative and postoperative parameters were compared using SPSS version 26. Results: Of the 70 patients, 31 were obese (21 males, 10 female) having mean age 37.7 ± 9.73 years and mean BMI 32.5 ± 1.1 kg/m². There were 39 non-obese subjects (25 males, 14 female) with mean age 47.1 ± 11.7 years and mean BMI 24.4 ± 1.32 kg/m². Mean length of hospitalization among obese patients was 4.65 ± 1.2 days compared to 3.0 ± 0.0 days among non-obese patients (p = 0.009). The difference in duration of surgery between obese and non-obese donors was significant (p < 0.001). Postoperative complications were less frequent among non-obese donors, but the difference was not significant (p = 0.144). Conclusion: Donors who were obese experienced major operating difficulties together with longer procedure durations and longer postoperative hospitalization. Key Words: Obesity, Living kidney donation, Surgical outcomes, Postoperative complications, Renal function.